PHARMACOLOGICAL TREATMENT OF ARTERIAL HYPERTENSION GUIDED BY PERIPHERAL OR CENTRAL BLOOD PRESSURE: COMPARISON OF THE TWO STRATEGIES IN THE INCIDENCE OF INTERMEDIATE OUTCOMES. (June 2022) - Filho, Gilberto Guimaraes; Inuzuka, Sayuri; Vitorino, Priscila; Sousa, Ana Luiza Lima; Coca, Antonio; Barroso, Weimar Sebba
Abstract : Objective: To compare the parameters of central and peripheral blood pressure measurements, arterial stiffness, target organ damage (TOD), biochemical and renal profiles among participants who had the therapeutic strategy guided by central (CG) and peripheral (PG) blood pressure values. Design and method: Randomized study in two groups: CG and PG. Five visits were carried out, the first (V1) being selection and randomization followed by intermediate visits, every 3 months, to assess blood pressure and adjust antihypertensive drugs. The procedures performed in the initial and final visit (V5) were: measurement of central arterial pressure and pulse wave velocity (PWV) (mobil-o-graph) and peripheral (OMRON HEM1100), carotid ultrasound, echodopplercardiogram and laboratory tests. Paired and unpaired t and chi-square tests were used. Adopted significance level of 5% and a confidence interval of 95%. Results: A total of 59 participants were evaluated (30 from the CG and 29 from the PG). Age, BMI, central and peripheral blood pressure measurements, PWV, left ventricular mass index (LVMI), carotid intimal mean thickness, biochemical profile and glomerular filtration rate did not differ between the two groups (p > 0.05) in randomization. The augmentation index (AIx) was higher in the CG than in the PG at randomization (27.3% ± 12.2% vs 20.3% ± 13.3% p 0.041). After 1 year of follow-up, in the analysis between the groups, the central diastolic pressure was lower in the CG (78.9mmHg ± 9.7mmHg vs 84.3 ± 10.4mmHg, p 0.024) and the difference in AIx between the groups ceased to exist. When intra-group comparisons were made before and after the intervention, a reduction in the PWV (p < 0.001) and LVMI (p = 0.018) was observed in the CG. In PG there was an increase in PWV (p < 0.001) and LVMI (p = 0.003). Conclusions: The intervention guided by central pressure, after 1 year of follow-up, was able to reduce the central diastolic pressure and correct the AIx parameter and, in the intra-group analysis, it promoted a reduction in PWV and LVMI. There was no difference between the two groups regarding the improvement of outcomes related to central and peripheral blood pressure, cardiac and vascular TOD, biochemical and renal profile.